UPAYA MENINGKATKAN MUTU SEKOLAH DASAR MENGHADAPI ERA REVOLUSI INDUSTRI 4.0. - Sunarijah, Sunarijah (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2018)
The development of the economic era of education 4.0 is a challenge in preparing quality and competitive human resources in the global era, the world of production and society, which is connected to it, changes faster and faster. oriented to the 4th industrial revolution. this change has an influence on the whole community and consequently the educational needs and methods of teaching / learning also change drastically. Improving the quality of education is a choice as well as the orientation of the development of national civilization as an investment in the future of long-term nation development. This orientation is absolutely done because education is believed to be the main means of developing the quality of human resources. The purpose of this article is to describe efforts to improve the quality of primary schools in the face of the Industrial Revolution Era 4.0 in the perspective of the role of School Supervisors. The results of the discussion are summarized as follows: 1) Criteria for learning quality target teaching outcomes that can be verified by students (process and results), which try to make the success of teaching measurable to students. The TIMSS scale is the latest example of a results-oriented estimation scale. 2) The concept of quality education is not simply focused on providing educational input factors, but rather paying attention to the educational process factors, but the input of education is an absolute must within certain limits but does not guarantee that it can automatically improve quality education. 3) In the context of 4.0 industrial revolution. The education system must create globalized students who can explore the world outside the immediate environment through investigating local, global, and cultural problems by recognizing, understanding and respecting the views of others, communicating cross-cultural ideas efficiently, effectively through involvement in interactions that right, open, and effective. 4) Supervisors in carrying out their main tasks in the school they are building are not to find fault as a basis for giving punishment but must be a partner of the school in fostering and developing the quality of education in schools so that school performance gradually increases towards achieving effective schools.